Penerapan dan Analisis Metode Social Network Analysis untuk Menentukan Rekomendasi Diskon dengan Menggunakan Library NetworkX - Iskandar, Ryan Agung; Edi, Sri Winarso Martyas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
At present technology has developed rapidly, especially in industrial technology. Business competition is getting tighter, making people have to find ways to maintain their business. One strategy that can be used is to provide discounts on goods or services sold. This discount can be made based on the company's sales data or other factors. In this case, the company has large sales data. Therefore, a way is needed to process the large sales data, and one efficient way to do this is to use the Social Network Analysis method. This study measures the degree of Information Centrality from the Social Network Analysis method to measure how much the item is purchased, this can be taken into consideration to determine discounts on goods or services sold. This research provides the results of discount recommendation applications that can process large sales data and provide recommendations based on the Social Network Analysis method.